CHEMICAL COMPOSITION AND ANTIOXIDANT ACTIVITY OF Pelargonium graveolens OIL - & Jaber, Obeid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A comparison was conducted between volatile oil of the plant parts leaves and stems of Pelargonium graveolens as antioxidant by using the compound DPPH as a free radical. This study aimed at isolation and diagnosis the active compounds of the volatile oil .The volatile oil was extracted by using the water distillation Clevenger .Volatile oils were detected by using the liquid gas chromatography. The results showed that 100 g of leaves and steams produced a volatile oil estimated by 5% and 2.3% respectively. The study has shown that volatile oil of leaves contains 12compounds and the highest was Terpineol reaching 31.52% , Camphor 7.06 % and Cis-alpha-Bisabolene 4.38%. The study showed that volatile oil in steams contains 10 compounds and Linalool represented the highest (3.00%), followed by Camphor (2.76 %), then (E) –B-Farnesene (2.31 %). The results also showed high volatile oil antioxidant activity in both leaves and steams at the concentration 125 µg ml-1 reached 100 % compared with Ascorbic Acid when studying the effect of their oxidative effect on the free radical DPPH, the results also indicate significant differences between the volatile oil concentrations in both leaves and steams.